Osteoid osteoma (OO) of the coracoid: a case report of arthroscopic excision and review of literature - Goyal, Saumitra (SICOT J, 2015)
Osteoid osteoma (OO) of the coracoid is a rare entity that may present with variable symptoms from shoulder leading to delay in diagnosis and treatment. We present the clinical and radiological findings and management of one such case along with a review of similar cases reported in the literature. There was a delay of 2 years in diagnosis, which was later confirmed by computed tomography in addition to magnetic resonance imaging (MRI). The lesion was accessed arthroscopically and excised by unroofing and curettage. “OO” should be included in the differential diagnosis of shoulder pain in young patients not responding to long-term conservative treatment. Arthroscopic excision and curettage provide a good choice for management, with low morbidity and rapid recovery.